SISTEM PERADILAN PIDANA TERPADU MERUPAKAN PERLINDUNGAN HUKUM YANG BERIMBANG - Ansori Ansori (Universitas Bondowoso, 2021)
The Sentencing of System, lack of consistency between laws and reality was criminogenic… Keyword : The Sentencing of Syatem, reality was criminogenic